Structural sensing, health monitoring, and performance evaluation - Huston, D. 1958- (Sensors series., 2011)
Structural health monitoring (SHM) uses one or more in situ sensing systems placed in or around a structure, providing real-time evaluation of its performance and ultimately preventing structural failure. Although most commonly used in civil engineering, such as in roads, bridges, and dams, SHM is now finding applications in other engineering environments, such as naval and aerospace engineering. Written by a highly respected expert in the field, ""Structural Sensing, Health Monitoring, and Performance Evaluation"" provides the first comprehensive coverage of SHM. The text begins with a review